A clinical perspective on muscle specific kinase antibody positive myasthenia gravis - Omar Keritam; Omar Keritam; Angela Vincent; Fritz Zimprich; Fritz Zimprich; Hakan Cetin; Hakan Cetin (Frontiers in Immunology)
The discovery of autoantibodies directed against muscle-specific kinase (MuSK) in “seronegative” myasthenia gravis (MG) patients marked a milestone in MG research. In healthy muscle, MuSK regulates a phosphorylation pathway, which is essential for the development and maintenance of acetylcholine receptor (AChR) clusters at the neuromuscular junction. Autoantibodies directed against MuSK are predominantly of the IgG4 subclass, but there is increasing evidence that IgG1-3 could also contribute to the pathology underlying MuSK-MG. MuSK-IgG4 are monovalent and block the binding site for LRP4 on MuSK, thereby inhibiting the downstream phosphorylation pathway and compromising the formation of AChR clusters. Clinically, MuSK-MG is commonly associated with the predominant involvement of bulbar, facial, shoulder and neck muscles. Cholinesterase inhibitors should be avoided in MuSK-MG due to the risk of clinical impairment and cholinergic crisis. Corticosteroids and other non-steroidal immunosuppressants are less effective with the need for higher doses and prolonged treatment. Rituximab, by contrast, has been shown to be particularly effective and is now often used early in the disease course. Its use is associated with a significant improvement in the clinical outcome of MuSK-MG patients over time. This review aims to describe the pathophysiology underlying MuSK-MG and provide a comprehensive overview of the clinical features and therapeutic options.